2020
DOI: 10.17159/caj/2020/30/2.8023
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution in Kigali, Rwanda: spatial and temporal variability, source contributions, and the impact of car-free Sundays

Abstract: Ambient air pollution, particularly fine particulate mass (PM2.5) and ozone (O3), is associated with premature human mortality and other health effects, but monitoring is scarce to non-existent in large parts of Africa. Lower-cost real-time affordable multi-pollutant (RAMP) monitors and a black carbon monitor were deployed in Kigali, Rwanda to fill the air quality data gap here. PM2.5 data were corrected using data from a coincident, short-term campaign that used standard filter-based gravimetry, while gas dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
4
21
1
Order By: Relevance
“…Surface concentrations and diurnal trends of ARISense CO and PM in Malawi were comparable to studies in Kenya, Rwanda, Ethiopia, Uganda and South Africa (Scheel et al, 1998;Toihir et al, 2015;Laakso et al, 2008;DeWitt et al, 2019;Subramanian et al, 2020;Nthusi, 2017;McFarlane et al, 2021) 500 ppb, at their rural and urban sites (Subramanian et al, 2020). Both studies of Rwanda found mean ambient O3 concentrations of 30 to 40 ppb (DeWitt et al, 2019;Subramanian et al, 2020). The annual mean ARISense O3 values were up to a factor of 10 lower, however, we identified quality assurance issues in the calibrated O3 values, particularly for the second half of the deployment data.…”
Section: Comparison To Other Ambient Measurements In Ssasupporting
confidence: 66%
“…Surface concentrations and diurnal trends of ARISense CO and PM in Malawi were comparable to studies in Kenya, Rwanda, Ethiopia, Uganda and South Africa (Scheel et al, 1998;Toihir et al, 2015;Laakso et al, 2008;DeWitt et al, 2019;Subramanian et al, 2020;Nthusi, 2017;McFarlane et al, 2021) 500 ppb, at their rural and urban sites (Subramanian et al, 2020). Both studies of Rwanda found mean ambient O3 concentrations of 30 to 40 ppb (DeWitt et al, 2019;Subramanian et al, 2020). The annual mean ARISense O3 values were up to a factor of 10 lower, however, we identified quality assurance issues in the calibrated O3 values, particularly for the second half of the deployment data.…”
Section: Comparison To Other Ambient Measurements In Ssasupporting
confidence: 66%
“…In contrast, the only other source of AQ data in the city at that time, an integrated filter sampler, did not detect these benefits. Integrated filter samplers collect the cumulative mass of pollutants over extended time intervals (in this case, a day), and so could not identify such time‐of‐day‐specific changes in AQ (Subramanian et al., 2020 ). Low‐cost sensors can also be used for temporary deployments after natural disasters.…”
Section: Satellites Low‐cost Sensors and Aq Forecastsmentioning
confidence: 99%
“…The forecasts also provide information when clouds or gaps in coverage limit the detection of pollutants by satellites (Figure 7 ), as well as between overpass times. Conversely, the lack of satellite data does not allow one to verify the forecasted values under cloudy conditions unless surface data, such as from low‐cost sensors, are available (e.g., Subramanian et al., 2020 ).…”
Section: Improving Stakeholder Use Of Nasa Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution spikes have a short lifetime, requiring monitoring in a smaller time resolution [19]. These spikes need to be monitored at each appearance not to affect the living.…”
Section: Introductionmentioning
confidence: 99%